Recruitment lessons learned from a tailored web-based health intervention Project Y.E.A.H. (Young Adults Eating and Active for Health). Issue 5 (3rd August 2015) - Brown, Onikia; Quick, Virginia; Colby, Sarah; Greene, Geoffrey; Horacek, Tanya M.; Hoerr, Sharon; Koenings, Mallory; Kidd, Tandalayo; Morrell, Jesse; Olfert, Melissa; Phillips, Beatrice; Shelnutt, Karla; et al.
Abstract : Purpose: – Recruiting college students for research studies can be challenging. The purpose of this paper is to describe the lessons learned in the various recruitment strategies used for enrolling college students in a theory-based, tailored, and web-delivered health intervention at 13 US universities. Design/methodology/approach: – The community-based participatory research (CBPR) model was used to develop a staged-tailored, web-based, randomized control trial, focussing on eating behavior, physical activity, and stress management. Participant feedback during baseline assessments was used to evaluate recruitment strategies. Findings: – Findings from this feedback suggest that traditional recruitment strategies, such as newspaper ads and flyers, may not be the best approach for recruiting college students; instead, web-based efforts proved to be a better recruitment strategy. Research limitations/implications: – This project included results from 13 US universities and thus may not be generalizable: more research is needed to determine successful recruitment methods for 18-24 years old college students. Originality/value: – This paper lessens the gap regarding successful recruitment strategies for 18-24 years old college students.